Democracy and the rise of women's movements in Sub-Saharan Africa - Fallon, Kathleen M. (Johns Hopkins University Press, 2008)
Reclaiming power -- Queenmothers, colonization, and the struggle for legitimacy -- Democracy in perspective -- The iron fist -- Capturing democracy -- Big men, small girls, and the politics of power -- Women on the move.